Efektivitas Pemanfaatan Media Pembelajaran Pahima (Papan Hitung Matematika) terhadap Hasil Belajar Matematika Siswa Kelas Dua Madrasah Ibtidaiyah (IAIN Kendari, 2023)
This research aims to determine the difference in learning outcomes between students of class II of MIS Asy-Syafi’iyah Kendari before treatment in the experimental class and the control class, to identify the difference in learning outcomes before and after treatment in the experimental class, and to assess the difference in learning outcomes after treatment between the experimental and control classes. This experimental study with a pretest-posttest control group design was conducted at MI MIS Asy-Syafi’iyah Kendari with a population consisting of all second-grade students. The research sample was determined using purposive sampling technique, with class II A as the control class and class II B as the experimental class. Data collection techniques included observation, tests, and documentation, while data analysis techniques involved descriptive analysis and inferential analysis. The results showed that there was no significant difference in learning outcomes between students in the experimental class and the control class before treatment. However, there was a significant difference in learning outcomes for students in the experimental class before and after treatment. Additionally, there was a significant difference in learning outcomes between students in the experimental class and the control class after treatment. Furthermore, the n-gain test results revealed that the average n-gain score percentage in the experimental class was 63.78%, categorized as moderately effective. These findings indicate that the mathematical counting board learning media is sufficiently effective in improving the learning outcomes of second-grade students at MIS Asy-Syafi’iyyah Kendari.Keywords: Mathematics learning outcomes, mathematical counting board media